The effect of dead clay contents on mechanical properties of foundry molding sands - Kandelous Jalali, Mehran (Graduate School, 2022)
Sand mold casting is one of the easiest and most common casting processes in foundries especially in Turkey. Since the mold is obtained from natural sources and is widely available all around the world, their demand is increasing gradually. In the sand-casting process, the base sand which in the most cases included silica sand is mixed with clay as a binder agent, water, and other additives in a fixed proportion to achieve an integrated mold. There are some vital characteristics of molding sand that play an important role in satisfactory foundry productions. This great importance certifies mold strength and durability to deformity of the weight of the pattern. The gas permeability is other importance to determines an ability of mold that it allows gases to escape to prevent internal pressure growth in the mold. In addition, thermal resistance is other remarkable property of a mold that indicates the refractoriness of mold particles to withstand heat without melting or vitrifying of sand. Besides, collapsibility is other notable factor of molding sand and a mold sand with good collapsibility demonstrates an easy shakeout process and prevent hot tearing defects. There are many other variables factors that influence on mechanical properties of molding sand, which include the size and shape of sand's grains, the binder type and water content, level of compaction, the metal melting point, and thermal expansion characteristics of sand. Apart from the contents mentioned about effective factors that influence on quality of molding sand, there is an unwanted phenomenon that almost all foundry companies have been experienced which in such a state they are commonly known as "dead clay. As a result, the effect of dead clay content in the molding aggregate and its effect on mechanical properties such as green compression strength and shatter index of ordinary molding sands is the main objective of this study. Metals and alloys have different melting point because their atomic binding energies are different from each other. As a result, a high temperature needs to destroy these atomic binding and this elevate temperature leads to burning the binder contents in the molding sand. Since, these binders are responsible for the strength of mold by burndown binder which is called dead clay forms a dead coating on the surface of sand particles and make it useless for further molding operations. Almost all clays heated to or over 800 ºC will have no bonding power and lose their plasticity due to the breakdown of their structure and the electrochemical bonding between the clay flakes no longer exists. Further, clay loses its crystal structure, and unwanted phase transformations such as cordierite, mullite, and cristobalite form what causes various types of casting defects such as scabs, rattails, and blowholes. In general, bentonite loses its property at 100-400 ºC by absorbing water rapidly and active clay converted to dead clay. This dead clay is not suitable for molding purposes and must be removed or kept low in order to prevent surface defects in mold sand. There is no way of removing the dead clay without removing at the same time the active clay and other fine-grained materials. However, this is obvious that adding some fresh sand and active clay could decrease the dead clay contents in total. In view of these observations, the study of the relative effect of the dead clay on the properties of green sand through the factorial design of statistical experiments seems to be quite justified. In this study, the different green sand mixtures with various dead clay contents consisting of especial sodium bentonite from Esan Eczacıbaşı Company Ltd, and silica sand from Kum Madencilik Company Ltd., have been investigated to determine an optimum amount of dead clay in the green sand mixture, what is acceptable content to achieve a suitable green sand molding property. Some amount of active clay (sodium bentonite) was fired at 800 ºC in an electric oven for about 3 hours to ensure the conversion of all active clay to dead clay. Further, to evaluate the realistic conditions, the reused molding sand mixtures with various dead clay contents have been prepared and applied for a small size pattern, then, the quality of molding has been determined. In addition, the verification of the findings which indicate the effects of dead clay content has been achieved by the investigation of physic-chemical, microstructural, and mechanical properties of the different green sand mixtures with various dead clay contents. For this aim, many analyses, such as the XRD, SEM, and TGA-DSC have been performed. The XRD analysis has been performed for the active sodium bentonite and its dead clay condition. The thermal behavior of the sodium bentonite has been determined by the TGA-DSC analysis. The SEM analysis has been performed for the dead clay particles surrounded by the silica sand particles. Therefore, the dead clay contents reduce the adhesion properties of sand particles and cause to decrease in the mold sand strength. It has been observed that increasing the dead clay content in green sand molding mixtures resulted in decreasing the green compression strength (GCS) and green shear strength (GSS) values gradually and the green sand loses its strength dramatically and dropped especially when the dead clay content increased over 2% of total clay content in green sand mixture with the total 7% bentonite. The experiments show that with increasing the dead clay content above 2%, the green sand strength decreases rapidly. The shatter index showed the same reaction as the moldability index when the dead clay content increased over 2% of the total amount of bentonite in the green sand mixtures. Both the shatter index and moldability index decreased substantially when dead clay content is added to green sand mixtures and it will be caused to create some defect in the surface of the mold. In addition, adding dead clay content had a different effect on the gas permeability index. Since dead clay particles have no binding ability therefore green sand particles lose their binding property as dead clay increases. As a result, permeability value showed a parallel relation with dead clay content such that increasing the dead clay content caused an increase destructively in the gas permeability. At the end of this investigation, the molding trial observations show after removing the pattern of the molding sand there were some cracks in the surface of the sample molds, and it determines clearly, the negative effect of the dead clay content on the molding sand which represents unsatisfactory casting productions. Thanks to this study, the required values for the best molding quality can be determined. In addition, the effect of dead bentonite on casting is clearly revealed. The data obtained as a result of this study has a very important place among the literature review, as well as a very important place for the foundries and the molding manufacturers.
Ölü bentonit içeriğinin döküm kalıp kumlarının mekanik özelliklerine etkisi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2022
Keywords: Activated clay; Aktif kil; Bentonite; Bentonit; Sand diesinking; Kum kalıpçılığı